2006
DOI: 10.1161/01.str.0000206439.62025.97
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Reactivity and Cognitive Decline in Patients With Alzheimer Disease

Abstract: Background and Purpose-The aim of this study was to explore the possible contribution of alterations in cerebral hemodynamics to the evolution of cognitive impairment in patients with Alzheimer disease (AD). Method-Fifty-three patients with AD were investigated. The evolution of cognitive decline over 12 months was evaluated by means of changes in Mini Mental State Examination (MMSE) and AD Assessment Scale for Cognition (ADAS-Cog) scores. Demographic characteristics, vascular risk profile, pharmacological tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
194
4
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(221 citation statements)
references
References 33 publications
15
194
4
5
Order By: Relevance
“…For example, several reports have shown that midlife overweight and obesity increased the risk of CD, VaD, and AD in late life [12-15, 48, 49]. It is now widely accepted that vascular and metabolic risk factors play an important role in the onset and progression not only of VaD, but also of AD and other dementias [50,51]. The magnitude of the effect is wider if they are present during midlife, maybe because their biological mechanisms need a long "window period" to determine the pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several reports have shown that midlife overweight and obesity increased the risk of CD, VaD, and AD in late life [12-15, 48, 49]. It is now widely accepted that vascular and metabolic risk factors play an important role in the onset and progression not only of VaD, but also of AD and other dementias [50,51]. The magnitude of the effect is wider if they are present during midlife, maybe because their biological mechanisms need a long "window period" to determine the pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for the RSFA approach (Kannurpatti et al, 2014), which we found to not be uniformly associated with standard CVR estimates. We argue the same for our parametricdeconvolution-based rs-qCVR estimates, as in many cases, such as in stroke ) and Alzheimer's disease (Silvestrini et al, 2006;Yezhuvath et al, 2012), CVR maps are used to depict local abnormalities rather than make statements regarding global differences between individuals. In such cases, it is more crucial that the spatial pattern rather than the absolute value of the CVR estimates be accurate, and therefore, calibration of the rs-fMRI CVR values is not necessary.…”
Section: Practical Considerations and Limitationsmentioning
confidence: 91%
“…55 Hence, impaired cerebral hemodynamics, as evaluated by transcranial Doppler ultrasonography, may reveal interesting information on the association between altered cerebrovascular hemodynamics and cognitive impairment. 56 Indeed, previous transcranial Doppler studies show a positive correlation between hemodynamic impairment and cognitive impairmentsuggesting that microvascular damage contributes to the cognitive changes observed in the early stages of dementia. 57,58 Additionally, the prevalence of traditional 2 This might explain the association between CKD and cerebrovascular disease because the latter plays the largest role in the pathogenesis of cognitive impairment in CKD patients.…”
Section: Potential Causes Of Cognitive Impairment In Patients With Ckdmentioning
confidence: 96%